2013
DOI: 10.1007/s11916-012-0312-9
|View full text |Cite
|
Sign up to set email alerts
|

Disposition and Adjustment to Chronic Pain

Abstract: Several empirical studies have shown that personal characteristics act as differential variables, which determine how pain is experienced and how the chronic pain patient adjusts to pain. The main aim of the present research is to review the relationships between some dispositional characteristics and pain adjustment. Taking into account the empirical literature, 6 personality traits that are relevant to the pain experience have been selected: neuroticism, anxiety sensitivity, and experiential avoidance as ris… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

1
27
0

Year Published

2013
2013
2023
2023

Publication Types

Select...
7
2

Relationship

1
8

Authors

Journals

citations
Cited by 44 publications
(28 citation statements)
references
References 94 publications
1
27
0
Order By: Relevance
“…The diagnosis of chronic pain requires that the condition lasts longer than 3–6 months. Chronic pain can be a debilitating condition with potentially devastating impact on the quality of life [2]. It occurs in a wide variety of conditions, including peripheral neuropathy, stump pain, phantom pain, complex regional pain syndrome, central pain, polymyalgia rheumatica, fibromyalgia, pain of psychological origin, and epilepsy.…”
Section: Introductionmentioning
confidence: 99%
“…The diagnosis of chronic pain requires that the condition lasts longer than 3–6 months. Chronic pain can be a debilitating condition with potentially devastating impact on the quality of life [2]. It occurs in a wide variety of conditions, including peripheral neuropathy, stump pain, phantom pain, complex regional pain syndrome, central pain, polymyalgia rheumatica, fibromyalgia, pain of psychological origin, and epilepsy.…”
Section: Introductionmentioning
confidence: 99%
“…Similar to catastrophizing, pain disability was significantly lower only among those in the lowest group of dispositional personality traits compared to the other two groups, while no significant difference was seen between the high and moderate groups. Ramírez-Maestre and Esteve [ 46 ] also found that personality traits including neuroticism, anxiety sensitivity, and experiential avoidance were risk factors for increased probability of disability among individuals with chronic pain. Mehta et al [ 47 ] identified subgroups of chronic pain individuals based on their levels of anxiety sensitivity and experiential avoidance.…”
Section: Discussionmentioning
confidence: 99%
“…In a recent review of personality and adjustment to chronic pain, Ramírez-Maestre et al suggest that assessment of personality may be beneficial when conducing a multidimensional evaluation of patients afflicted with chronic pain disorders, particularly with regard to patient optimism and additional active coping responses that have previously been observed in higher-extraversion subjects. 30 This builds upon the group's earlier work in which neuroticism was associated with passive coping strategies in the context of chronic pain. 31 The authors therefore conclude that a greater understanding of patient personality characteristics may assist in the design of pain-intervention programs, as well as potentially aiding in prognosticating treatment outcomes.…”
Section: Effects Of Personalitymentioning
confidence: 92%
“…31 The authors therefore conclude that a greater understanding of patient personality characteristics may assist in the design of pain-intervention programs, as well as potentially aiding in prognosticating treatment outcomes. 30 It is hoped that, with further research elucidating the effect of interindividual factors (including personality) on esophageal pain, modern efficacious treatments may be developed, for instance, within the recent concept of personalized medicine.…”
Section: Effects Of Personalitymentioning
confidence: 99%